Unraveling the digital technologies and banking inclusion nexus in Sub Saharan Africa: What causality for what heterogeneity? - Bédi Guy Hervé Drama; Melain Modeste Senou (Discover Sustainability)
Abstract This study investigates the causal relationship between Information Technologies (IT) and banking inclusion across 45 Sub-Saharan African (SSA) countries from 2000 to 2023. Utilizing a simultaneous equations framework to address potential endogeneity, we assess the impact of mobile phone and internet penetration on financial access while accounting for institutional and socioeconomic factors. Employing Three-Stage Least Squares (3SLS) and Seemingly Unrelated Regression Equations (SURE) estimators, our findings reveal that IT adoption significantly enhances banking inclusion through multiple mechanisms. Specifically, mobile phone penetration fosters financial access by expanding mobile banking solutions, while internet penetration supports the digitalization of financial services, reducing distance and cost barriers. Furthermore, complementary investments in telecommunications infrastructure, human capital, and electricity supply amplify these effects. This study underscores the need for policymakers to integrate digital transformation strategies into financial inclusion policies, bridging both financial and digital divides to enhance economic participation and resilience in SSA.